1999
DOI: 10.1109/18.761335
|View full text |Cite
|
Sign up to set email alerts
|

The modeling and estimation of statistically self-similar processes in a multiresolution framework

Abstract: Abstract-Statistically self-similar (SSS) processes can be used to describe a variety of physical phenomena, yet modeling these phenomena has proved challenging. Most of the proposed models for SSS and approximately SSS processes have power spectra that behave as 1=f , such as fractional Brownian motion (fBm), fractionally differenced noise, and wavelet-based syntheses. The most flexible framework is perhaps that based on wavelets, which provides a powerful tool for the synthesis and estimation of 1=f processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…We limit our treatment to those aspects required for subsequent development; the reader is referred to other literature (e.g., [8,12,18,33] for further details of these models, and their application to a variety of 1-D and 2-D statistical inference problems.…”
Section: Multiscale Stochastic Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…We limit our treatment to those aspects required for subsequent development; the reader is referred to other literature (e.g., [8,12,18,33] for further details of these models, and their application to a variety of 1-D and 2-D statistical inference problems.…”
Section: Multiscale Stochastic Processesmentioning
confidence: 99%
“…(2) are called multiscale autoregressive (MAR) processes. It has been shown that the MAR framework can effectively model a wide range of Gaussian stochastic processes, including one-dimensional Markov processes [31,33], 1/f -like processes [8,11,12,32,60], and Markov random fields [32,33]. An additional benefit of the MAR framework is that it leads to extremely efficient algorithms for estimating the process x(s) on the basis of noisy observations of the form y(s) = C(s)x(s) + v(s), where v(s) is a zero-mean, white noise process with covariance R(s).…”
Section: Q(s) B(s)b T (S)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that this framework can capture a very rich class of phenomena, ranging from one-dimensional Markov processes to 1/f -like processes [13] and Markov random fields (MRFs) [14].…”
Section: Image Representationmentioning
confidence: 99%
“…Finally, imposing a simple statistical structure also makes it feasible to estimate the parameters of the model [80,70]. First, the statistical structure imposed greatly reduces the number of parameters necessary for the model, and additional prior knowledge can be brought to bear on how the parameters are themselves interrelated.…”
Section: Multi-scale Tree-structured Modelsmentioning
confidence: 99%